To explore the relationship between physical activity and sleep quality of college students based on the mediating effect of stress and subjective well-being - Jinling Yin; Xiaolei Cheng; Zhenxiu Yi; Liping Deng; Yang Liu (BMC Psychology)
Abstract Promoting the physical and mental health of college students is an inevitable requirement of the global health perspective. Given the close relationship between physical activity, sleep, and mental health, this study explores the mediating role of mental health in the relationship between physical activity and sleep quality. A cross-sectional study was conducted among 4,706 college students, who self-reported their levels of physical activity, stress, subjective well-being, and sleep quality. The results showed that physical activity significantly and positively predicted sleep quality (β = 0.106, SE = 0.016, p < 0.001), and this positive predictive effect remained significant after the inclusion of mediating variables (β = 0.072, SE = 0.013, p < 0.001). Stress and subjective well-being acted as mediating factors between physical activity and sleep quality, forming a chain mediation effect. This study reveals the multiple benefits of physical activity for the development of college students and suggests that society, schools, families, and individuals should actively explore ways and means to engage in physical activity and exercise regularly. Future research is recommended to investigate the longitudinal changes in mental health between physical activity and sleep quality.